An overlapping window decorrelating multiuser detector for DS-CDMA radio channels. - Xiafeng Wang (IEEE Transactions on communications)
A new multiuser detector for direct-sequence code-division multiple-access communication systems is described. The proposed detector divides the received signal stream into a number of overlapping windows and decorrelates them window by window. This scheme is justified by an analysis of the convergence and decay rate of the impulse response. Based on the results, a signal-adapted criterion is developed which enables one to determine the window length according to the near-far situation of a practical system. A performance analysis and simulation results show that a small to moderate window length is usually sufficient to yield a performance that is close to or even better than that of the ideal decorrelating detector